FOXA2/miR-148a-3p/SMURF2 signaling feed-forward loop alleviates spinal cord ischemia-reperfusion injury-induced neuropathic pain by modulating microglia polarization in rats - Hao, Xiaotong; Cao, Linyan; Li, Jinshi; Lei, Qian; Liu, Xuan; Li, Yuanyuan; Fan, Yiting; Xu, Jingjing; Fang, Bo (Frontiers in Immunology, 2025)
BackgroundMicroglia polarization is crucial in mediating neuropathic pain. However, the role of microglia polarization in regulating spinal cord ischemia-reperfusion injury (SCIRI)-induced neuropathic pain is largely unknown. This study aimed to elucidate the relationship between SCIRI-induced neuropathic pain and microglia polarization, as well as the underlying mechanisms, with the objective of identifying potential therapeutic targets.MethodsA rat model of SCIRI was established by aortic arch clamping, then pain thresholds were measured. In vitro, oxygen-glucose deprivation/reperfusion (OGD/R) of HAPI microglia was performed. The expressions of sirtuin1 (SIRT1), SMAD specific E3 ubiquitin protein ligase 2 (SMURF2), and markers of microglial polarization (CD206, iNOS) were quantitated by Western blot and immunofluorescence, and the levels of cytokines (TNF-α, IL-4) were assessed by Enzyme-linked immunosorbent assay (ELISA). Real-time quantitative reverse transcription PCR (RT-qPCR) experiments were conducted to quantify the levels of miR-148a-3p and FOXA2. Dual-luciferase reporter assay was employed to identify the targeted regulation of SMURF2 by miR-148a-3p and the transcriptional regulation of miR-148a-3p by FOXA2. The regulatory role of FOXA2 in the transcription of miR-148a-3p was validated using chromatin immunoprecipitation (ChIP). In addition, co-immunoprecipitation (Co-IP) assays were performed to confirm the binding relationship between SMURF2 and FOXA2. And the ubiquitination levels of FOXA2 and SIRT1 were measured. Subsequently, rats were administered miR-148a-3p to assess pain thresholds. Western blot and immunofluorescence quantitative analysis was conducted to assess the expression of markers associated with microglia polarization.ResultsSCIRI significantly reduced mechanical and thermal pain thresholds in rats and promoted microglial polarization, with a concomitant decrease in SIRT1 expression and an increase in SMURF2 expression in microglial cells. Further analysis revealed that upregulation of miR-148a-3p promoted microglia polarization toward M2 by targeting SMURF2, which in turn inhibited ubiquitination of SIRT1. FOXA2 was an upstream transcription factor of miR-148a-3p and SMURF2 bound to FOXA2, resulting in its ubiquitination. Finally, in vivo experiments demonstrated that miR-148a-3p effectively promoted microglia transformation from M1 to M2 and reduced neuropathic pain following SCIRI.ConclusionsThe FOXA2/miR-148a-3p/SMURF2 signaling feed-forward loop regulates SIRT1 levels and thereby exerts control over microglia polarization and the regulation of SCIRI-induced neuropathic pain.